2022
DOI: 10.1002/pmic.202200155
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analyses reveal the impact of nitrogen starvation on the proteome of the model diatom Phaeodactylum tricornutum

Abstract: Diatoms are one of the largest groups in phytoplankton biodiversity. Understanding their response to nitrogen variations, present from micromolar to near-zero levels in oceans and fresh waters, is essential to comprehend their ecological success. Nitrogen starvation is used in biotechnological processes, to trigger the remodelling of carbon metabolism in the direction of fatty acids and triacylglycerol synthesis. We evaluated whole proteome changes in Phaeodactylum tricornutum after seven days of cultivation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…With the increasing salinisation of water bodies and scarcity of freshwater resources, algae such as Microcystis aeruginosa , Scenedesmus obliquus , Isochrysis galbana Parke and Tribonema minus are considered as the best raw materials for the development of sustainable energy production [ 68 , 69 ]. Studies have shown that Microcystis aeruginosa has a simple composition of lipids and fatty acids that can be easily transesterified to biodiesel [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing salinisation of water bodies and scarcity of freshwater resources, algae such as Microcystis aeruginosa , Scenedesmus obliquus , Isochrysis galbana Parke and Tribonema minus are considered as the best raw materials for the development of sustainable energy production [ 68 , 69 ]. Studies have shown that Microcystis aeruginosa has a simple composition of lipids and fatty acids that can be easily transesterified to biodiesel [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phaeodactylum tricornutum as a model organism for diatom, the proteomics of is mainly focused on carbon and nitrogen metabolism, fatty acid and lipid synthesis of diatoms under N and P limiting conditions. The intracellular changes in Phaeodactylum tricornutum under different conditions were revealed at the protein level, such as the increase of plastidial palmitoyl- ACP desaturase, which is an important marker of carbon metabolism towards fatty acid and triacylglycerol synthesis [ 17 20 ]. Dunaliella salina is often used as a model algal species for halophilic algae and the molecular mechanisms of its salt tolerance indicated that salinity-regulated proteins were mainly involved in the Calvin cycle, energy production, protein synthesis/degradation, membrane structure stabilisation and signal transduction pathways [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%